2021
DOI: 10.1021/acs.jafc.1c03582
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Carbonyl Compounds for Unveiling Protective Mechanisms of Pueraria lobata against Diabetic Nephropathy by UPLC-Q-Orbitrap HRMS/MS Analysis

Abstract: Carbonyl compounds play a critical role in the pathogenesis of diabetic nephropathy (DN). Pueraria lobata (PL), also known as “Kudzu”, is a widely consumed functional food or nutraceutical and has shown promise in the prevention of diabetes and complications such as DN. To explore the beneficial effects and the underlying mechanisms of PL against DN, a new strategy for in-depth metabolic profiling of carbonyl compounds in DN mice plasma by chemical derivatization combined with UPLC-Q-Orbitrap high-resolution m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…AGEs are macromolecules generated by the Maillard reaction and can induce carbonyl stress. 48,49 Histopathological studies indicated that AGEs, formed and accumulated in vivo, play a pivotal role in the development of diabetes and its complications. 50 Whether DST can improve diabetes and its complications through AGEs still requires more research.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…AGEs are macromolecules generated by the Maillard reaction and can induce carbonyl stress. 48,49 Histopathological studies indicated that AGEs, formed and accumulated in vivo, play a pivotal role in the development of diabetes and its complications. 50 Whether DST can improve diabetes and its complications through AGEs still requires more research.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…In this experiment, for DCI mice, the level of LPS, the protein expression of TLR4, MyD88, and p‐p65, and the levels of IL‐6 and IL‐1β in the colon and brain, as well as the protein expression of RAGEs in brain were higher than those of normal mice, indicating that there are intestinal inflammation and neuroinflammation in DCI mice. In addition, some abnormal biochemical indicators (Ach, MDA, SOD, and AGEs), the increase in GFAP and Iba‐1, and the loss of DN can also prove the existence of neuroinflammation in DCI mice (Chang et al, 2022; Kim & Song, 2020; La Barbera et al, 2021; Zhang, Guo, et al, 2021). Correlation analysis also showed a strong positive correlation between intestinal inflammation and neuroinflammation, consistent with previous studies (Welcome, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As one of the crucial microvascular complications of DM, DN is also the primary cause of chronic kidney disease and end-stage renal disease (ESRD) . Pathological changes include glomerulosclerosis, mesangial cell hypertrophy, thickening of basement membranes, and renal fibrosis. Currently, the treatments for DN focus on controlling glycaemic, controlling blood pressure with renin-angiotensin-aldosterone system inhibitors, and improving lifestyle. In addition, the discovery of some new targets also contributes to the research and development of DN new drugs, such as podocyte-endothelial communication .…”
Section: Therapeutic Mechanisms Of Hesperetin On Diabetes and Related...mentioning
confidence: 99%